Psychopathology of witchcraft, alienation and word of the ancestor : pyschological and sociocultural transmission in the Togolese filiation to the test of modernism - (:unkn) unknown (My University, 2023)
Over the last decades, Sub-Saharan Africa has been going through major sociocultural transformations on its territory, building its own modernism on the remnants of colonization as well as on the wave of globalization. The problem of African modernity lies in its power of rupture against a tradition (that is the law of the ancestors), which structures it and gives substance to both individual and collective identities. In Occident, a drop in religious beliefs combined with a disenchantment of the world had signed the access to modernity. On the contrary, one may observe, on the African continent, a bewitchment of the world, through a strengthening of the spiritual imagination and the use of witchcraft. For several years, we have worked in mental health centers in Togo. At first, we had decided to focus our research on patients who had manifested an acute psychotic episode. The said patients and their families not only use imaginary cultural representations but also witchcraft etiology in order to put their mental suffering into words. Guided by an empririco-inductive research method and by an ethnopsychoanalytical device, we have combined clinical interview techniques with the projective mediation of the free realization of the family tree. In that respect, our research moved away from the acute psychosis clinics in order to come closer to what we have chosen to call the psychopathological clinics of witchcraft. Thus, our thesis consists of studying the stakes of psychic transmission and sociocultural transmission in the psychopathological clinic of witchcraft, in a traditionalmodern Togolese context. Therefore, we offer to discuss, through psychopathology of witchcraft, how the subject uses both cultural and groupfamily representations of witchcraft to make sense of non-elaborated and conflicting internal experiences. Our results highlight experiences of psychic alienation, echoing with intersubjective and intrapsychic conflicts, as well as experience
Keywords: African Research